Hypospadias with dorsal chordee: Case report of a novel approach for correction - Shivaji B Mane; Jamir D Arlikar; Suyodhan Reddy; Nitin P Dhende (Wolters Kluwer Medknow Publications, 2011)
We report a novel surgical technique for correction of dorsal chordee with coronal hypospadias. The bulbar elongation and anastomotic meatoplasty procedure gave an excellent cosmetic and functional outcome.